Perancangan Destination Branding Sebagai Sarana Desa Pariwisata Dan Budaya - Aprilhani Suparyono, Zellita; Eka Nastiti, Nisa; Alifaprilina Supriadi, Olivine (KALATANDA : Jurnal Desain dan Media Kreatif, 2024)
Indonesia’s cultural diversity is enormous, not only culture but history, and also united customs. Jelekong Arts Village is a village in Bandung Regency which has an abundance of cultural and artistic diversity, the people of Jelekong themselves have also been trained in arts that have been passed down from generation to generation. Examples of culture and art in the Jelekong Art Village include painting craftsmen, Wayang Golek craftsmen, and even Wayang Golek performances. However, unfortunately, interest in visitors to the Jelekong Art Village has greatly decreased and the people there do not have strong and interesting information media, so that many Jelekong people have not continued their culture and art and there are still many people from Bandung and outside Bandung who do not know about the Jelekong Art Village. With this, the research that has been carried out uses a qualitative method which is based on the theory of Visual Communication Design by obtaining data through observation activities, surveys, question and answer activities with the Jelekong community and literature regarding the Jelekong Art Village. With the final result in the form of destination branding as an information medium for the Jelekong Arts Village so that the people of Bandung and also outside Bandung have an interest in the Jelekong Arts Village and have a lot of curiosity about the Jelekong Arts Village.